Unjust restitution: a century of black struggle for equality - Brown, Michael K. (University of California Press, 2025)
"The question of economic justice for Black Americans remains unresolved and continues to be the subject of contentious political debate. In Unjust Restitution, Michael K. Brown examines the meaning of racial equality during three transformative periods in American history, when significant changes to economic status and opportunity appeared to be a real possibility in the US: Reconstruction, the New Deal, and the Great Society. Political leaders believed slavery and Jim Crow degraded Black people and enacted policies to rehabilitate formerly subjugated individuals. Black Americans challenged this conception and repudiated the idea that they were damaged people in need of repair. Repeatedly, Black people's vision of economic justice was based on anti-privilege egalitarianism, the idea that a just restitution for their oppression required abolishing the political and legal privileges whites had acquired. Black opposition reveals what was at stake at each historical moment and what might constitute economic justice in the twenty-first century. Equality of opportunity can be a just restitution for continuing durable racial inequality only if it changes the structure of people's economic opportunities"--